Changes in key volatile components associated with leaf quality of Pandanus amaryllifolius Roxb. alongside growth duration - Lu Yan; Ang Zhang; Xiaowei Qin; Huan Yu; Xunzhi Ji; Shuzhen He; Ying Zong; Chunhe Gu; Zhen Feng; Lisong Hu; Zhiqing Lu (Food Chemistry: X)
Pandan (Pandanus amaryllifolius Roxb.) are one of the traditional food materials in Southeast Asian countries. However, there has long been a lack of understanding of the differences in volatile organic compounds (VOCs) of leaves at different growth periods. Gas chromatography-mass spectrometry (GC–MS) was used to identify and analyze VOCs in different leaf positions of Pandan in this study. The content of 2-Acetyl-1-pyrroline (2AP) was higher in L1-L3 and decreased with leaf growth, while squalene showed the opposite trend. The content of neophytadiene first increased and then decreased, reaching the highest in L15. L8 is the critical point at which the content of each major VOCs is balanced. Combining agronomic traits and VOCs content, leaves in L4-L25 position are suitable for harvesting. This study provides data support for scientific judgment of the harvesting site and time of Pandan, and provides theoretical basis for further utilization of VOCs of Pandan.